2018
DOI: 10.1016/j.compstruct.2018.05.103
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between nacre-like CFRP mesolayers and long-fibre interlayers

Abstract: In this paper, a carbon-fibre/epoxy (CF) composite with nacre-inspired tiled micro-structure is designed and synthesised. The aim is to investigate the interaction between the CF discontinuous micro-structure and continuous glass-fibre/epoxy (GF) layers, which are intended to act as crack stoppers, similarly to the organic interlayers that separate layers of ceramic tiles in natural nacre. Firstly, we use a GF skin to trigger unstable failure in nacre-like mesolayers, and show how the damage mode in the latter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The fractal patches demonstrated to successfully promote damage diffusion of the CFRP tiles while preserving the interface strength, therefore mimicking some of the toughening mechanisms of naturally-occurring nacre-like microstructures. Aiming at further enhancing the damage diffusion capability of HPFR nacre-like structures, Narducci et al [162] showed that hybridising a CFRP nacre-like microstructure with mesolayers of continuous glass fibres (Figure 13a) leads to enhancing the damage resistance of the composite. Fracture is stabilised through gradual pull-out of tiles (Figure 13b).…”
Section: Nacre-inspired Hpfrpsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fractal patches demonstrated to successfully promote damage diffusion of the CFRP tiles while preserving the interface strength, therefore mimicking some of the toughening mechanisms of naturally-occurring nacre-like microstructures. Aiming at further enhancing the damage diffusion capability of HPFR nacre-like structures, Narducci et al [162] showed that hybridising a CFRP nacre-like microstructure with mesolayers of continuous glass fibres (Figure 13a) leads to enhancing the damage resistance of the composite. Fracture is stabilised through gradual pull-out of tiles (Figure 13b).…”
Section: Nacre-inspired Hpfrpsmentioning
confidence: 99%
“…The zoom-in of the region where failure developed highlights the presence of stable pull-out mechanism of the nacre-like microstructure as well as the activation of a crack arrest mechanism due to the presence of the glass meso-layers. Reproduced and adapted from [162] with permission from Elsevier.…”
Section: Nacre-inspired Hpfrpsmentioning
confidence: 99%
“…When the nacre structure fails, the crack must run around the platelets rather than through them, increasing the length of the crack path and resulting in a higher work of fracture [ 29 ]. The structure has been exploited in various ways to improve the toughness of fibre composites, for example, for the development of strong and stiff carbon ‘super nanotubes’ that could be embedded in a softer polymer matrix [ 30 ] or a multilayer laminate composite of discontinuous carbon fibre layers and continuous glass fibre layers [ 31 ]. Another development was to laser-cut a tiled micro-structure with high accuracy and repeatability at the micro-scale (tiles of the order of 600 mm) onto thin-ply carbon/epoxy prepregs following the nacre model [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Milwich et al [10] highlights a fundamental aspect of biomimetics: biomimetics should be used to address engineering problems with the help of Nature's wisdom without it being reduced to a blind mimic of the observed structures. In this context, the presence of staggered arrangements of discontinuous stiff inclusions aligned along the loading direction, a recurrent feature in nacre-like and bone microstructures [11,12], has been a successful source of inspiration for the design of CFRPs microstructure with enhanced damage tolerance [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of extensive pull-outs was found to be one of the major causes of such a large increase in energy dissipation (up to 64% of the total work of fracture). Narducci et al [15][16][17] manufactured a nacre-like CFRP microstructure showing that the use of carefully designed discontinuities forming a tiled microstructure can lead to crack deflection, stable failure and damage diffusion under three-point bending of CFRPs and GFRP/CFRP tiled composites.…”
Section: Introductionmentioning
confidence: 99%